Inhalation Bioaccessibility of Polycyclic Aromatic Hydrocarbons in Fly Ash Generated From Petroluem Products and Waste Tyres - Nwafor Hanachor; Boisa Ndokiari; Konne Lelesi; Patrick Amaibi (Journal of Health and Environmental Research, 2026)
The inhalation of fine particulate matter (PM) containing polycyclic aromatic hydrocarbons (PAHs) poses significant health and environmental risks due to the potential bioaccessibility of these toxic compounds in the human respiratory system. This study investigates the inhalation bioaccessibility of PAHs associated with fly ash produced from the combustion of petroleum-derived fuels (local diesel, pure diesel, kerosene, asphalt, and crude oil) and waste tyres. Fly ash samples were collected from the different sample materials and analyzed for 16 priority PAHs using gas chromatography-mass spectrometry (GC-MS). The extent to which a substance becomes available for absorption in the body was assessed using artificial lysosomal fluid (ALF) to simulate human lung conditions over exposure periods from 48 hours up to 96 hours. The results revealed that high-molecular-weight PAHs such as benzo [a] pyrene (BaP), fluoranthene, and pyrene were the most bioaccessible, particularly in fly ash from pure diesel and tyre combustion. the degree to which polycyclic aromatic hydrocarbons (PAHs) in fly ash from different petroleum products and waste tyres are available for absorption in the body, varied significantly across fuel types, with waste tyre and diesel fly ash exhibiting the highest values. The findings underscore the importance of considering inhalation bioaccessibility when assessing the health risks of airborne PAHs from combustion sources. This study provides critical insights for air quality management and emphasizes the need for stricter controls on emissions from petroleum product use and waste tyre incineration.